2018
DOI: 10.12681/jhvms.15868
|View full text |Cite
|
Sign up to set email alerts
|

Effect of genistein addition to equine sperm freezing extender

Abstract: Cryopreservation negatively affects equine sperm quality post-thaw: an excessive release of reactive oxygen species (ROS) and increased protein tyrosine phosphorylation (known as cryocapacitation) have been demonstrated in frozenthawed equine sperm diminishing its lifespan. The objective of this study was to determine the possible beneficial effect of genistein addition (a ROS scavenger and protein tyrosine kinase inhibitor) to a commercial freezing extender. Equine sperm were frozen in the presence of differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…The effect of genistein upon equine semen quality has also been observed, with the addition of genistein to equine sperm (up to 800 µM) not significantly influencing viability [ 86 ]. Genistein also did not affect sperm motility or acrosomal status immediately and up to one hour after thawing [ 86 ]. It can be concluded that the beneficial effect of genistein on sperm motility is species-specific and may also be breed-specific.…”
Section: Effects On Male Reproductive Physiologymentioning
confidence: 99%
“…The effect of genistein upon equine semen quality has also been observed, with the addition of genistein to equine sperm (up to 800 µM) not significantly influencing viability [ 86 ]. Genistein also did not affect sperm motility or acrosomal status immediately and up to one hour after thawing [ 86 ]. It can be concluded that the beneficial effect of genistein on sperm motility is species-specific and may also be breed-specific.…”
Section: Effects On Male Reproductive Physiologymentioning
confidence: 99%
“…Martinez-Soto et al (2010) genistein is an isoflavone compound that has a direct effect on the function of mature spermatozoa by modifying the capacitation process and acrosome reaction. Genistein modifies membrane hemodialysis and causes a significant reduction in ROS (Garcia et al, 2015). On the other hand, genistein has a protective antioxidant effect on sperm DNA integrity.…”
Section: Discussionmentioning
confidence: 99%
“…Kumi-Diaka et al [ 233 ] stated that low doses of GEN (30 μg/mL) did not affect mice sperm motility, however its high concentrations (70 and 100 μg/mL) interfered with the sperm motion behavior. According to Macías-García et al [ 234 ], none of the GEN doses tested (0–800 μmol/L) had any effect in frozen-thawed equine sperm motility or viability. The fact that the addition of GEN did not significantly improve the basic quality parameters of semen led to the assumption that excessive ROS production prior, or during freezing may not be the main factor affecting equine sperm vitality exposed to low temperatures in comparison to cold or osmotic shock.…”
Section: Genisteinmentioning
confidence: 99%
“…Furthermore, besides differences related to an adequate GEN concentration, another question that needs to be considered, is related to the possibility that different mechanisms are responsible for induced capacitation of fresh or cryopreserved spermatozoa. Indeed, in case of frozen bull or equine spermatozoa, the biomolecule did not affect tyrosine phosphorylation or the acrosome status [ 234 , 240 , 241 ], suggesting that the process of cryopreservation per se affects the regulatory mechanisms of capacitation.…”
Section: Genisteinmentioning
confidence: 99%